Robust Water-Management Strategies for the California Water Plan Update 2013 Proof-of-Concept Analysis - Groves, David G. (RAND Corporation, 2013)
This report describes a proof-of-concept analysis using Robust Decision Making to evaluate water resource management response packages for California's Central Valley under future uncertainty. This analytic approach will be used to develop a more comprehensive analysis for the California Water Plan Update 2013.